Toward a Liturgical Existentialism - Rivera, Joseph (New blackfriars, 2013)
A liturgical existentialism attempts to situate Christian spirituality in view of a post-Heideggerian world. To this end, French phenomenologist Jean-Yves Lacoste has undertaken what is perhaps the most sustained analysis of Heideggerian existential phenomenology from a theological-mystical point of view, and this paper highlights his major achievement: the liturgical reduction. Certainly existentialism, after Heidegger, makes the “world” an object of inquiry, and yet Lacoste's reduction is problematic precisely because it privileges an ascetic spirituality that desires to “bracket” the world. Both the temporality and topology of the liturgical reduction are exposed to view in order to show that a liturgical existentialism properly conceived, does not bracket the world, but is realized carefully in and through the world-horizon itself.